Inhibition of inducible nitric oxide synthesis by catalposide from Catalpa ovata - Oh, H; Pae, HO; Oh, GS; Lee, SY; Chai, KY; Song, CE; Kwon, TO; Chung, HT; Lee, HS (GEORG THIEME VERLAG KG, 2002)
Catalposide (1) and two related iridoids were isolated from the stem of Catalpa ovata (Bignoniaceae) by bioassay guided fractionation. Catalposide (1) significantly inhibited the production of nitric oxide (NO) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages in a dose-dependent manner. RT-PCR and Western blot analyses demonstrated that catalposide (1) suppressed the expression of inducible nitric oxide synthase (iNOS) gene and iNOS protein. Catalposide (1) also inhibited the activation of LPS-induced NF-kappaB as analyzed by electrophoretic mobility shift assay (EMSA). In addition to the inhibitory effect on NO production in LPS-stimulated RAW 264.7 cells, catalposide (1) significantly inhibited the NO production in cytokine-stimulated human DLD-1 and rat vascular smooth muscle (VSM) cells in a dose-dependent manner.
Keywords: IRIDOID GLYCOSIDE; TRANSCRIPTION; SYNTHASE